A SABEDORIA de ROSVITA DE GANDERSHEIM: PROTAGONISMO FEMININO NO TEATRO ROSVITIANO - SILVA, ZARQUEU MANOEL DA (2021)
We used as a source of analysis, the piece Wisdom of Rosvita by Gandersheim, translated by Jean Luis Lauand (1986). The play tells the story of Santa Wisdom (Santa Sofia) and his three daughters called Faith, Hope and Charity, which are denounced to Emperor Hadrian by Antiochus. After being killed (beheaded), Christ answers the prayers of Wisdom, which ascends to heaven together with his daughters. Rosvita was a Benedictine nun of Saxon origin and lived a large part of her life in Gandersheim Abbey, being the first woman on record, writing epic poems and the first German writer in Latin. Like Rosvita, we list other women who played fundamental roles in the Middle Ages and whose writings still serve as “corpus” for various researches. We aim to highlight the role of female characters, based on the theory of female criticism and the decolonial proposal, having as a theoretical foundation the definition developed by researcher Luciana Deplagne (2019) and feminist literary criticism approached by the writer Milagros Garretas (1990). After theoretical exposition and clippings of the play that show the female protagonism, it is concluded that it is more than necessary to promote research and studies about the writings of female authorship, so that we can return their voices, now taken by the patriarchal society, which oppressed and subjugated them, having as historical debt the “decolonization” of these women and their works, placing them on an equal footing with all other writings acclaimed by literary criticism.